2009
DOI: 10.1161/circresaha.108.190587
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein Transport Through Aortic Endothelial Cells Involves Scavenger Receptor BI and ATP-Binding Cassette Transporter G1

Abstract: Abstract-Cholesterol efflux from macrophage foam cells is a rate-limiting step in reverse cholesterol transport. In this process cholesterol acceptors like high-density lipoproteins (HDL) and apolipoprotein (apo)A-I must cross the endothelium to get access to the donor cells in the arterial intima. Previously, we have shown that apoA-I passes a monolayer of aortic endothelial cells (ECs) from the apical to the basolateral side by transcytosis, which is modulated by the ATP-binding cassette transporter (ABC)A1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
152
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(172 citation statements)
references
References 36 publications
14
152
1
Order By: Relevance
“…There is cell culture evidence that lipid-free apoA-I binds to specific saturable high-affinity binding sites on aortic endothelial cells, which is followed by internalization, transcytosis, and delivery of lipidated apoA-I to the basolateral side . A similar phenomenon was observed when cultivated aortic endothelial cells were treated with mature HDLs (Rohrer et al 2009). However, the mechanisms involved in regulating this endothelial transport of apoA-I and HDLs are not fully understood.…”
Section: Transendothelial Hdl Transportsupporting
confidence: 69%
See 1 more Smart Citation
“…There is cell culture evidence that lipid-free apoA-I binds to specific saturable high-affinity binding sites on aortic endothelial cells, which is followed by internalization, transcytosis, and delivery of lipidated apoA-I to the basolateral side . A similar phenomenon was observed when cultivated aortic endothelial cells were treated with mature HDLs (Rohrer et al 2009). However, the mechanisms involved in regulating this endothelial transport of apoA-I and HDLs are not fully understood.…”
Section: Transendothelial Hdl Transportsupporting
confidence: 69%
“…Induction of ABCA1 expression by a combination of oxysterol and 9-cis-retinoic acid increased the binding and internalization of apoA-I in endothelial cells, whereas knockdown of endothelial ABCA1 by RNA interference reduced the cellular uptake and transcytosis of apoA-I ). Conversely, siRNA-mediated gene silencing experiments revealed that the cell surface binding and transport of HDLs through aortic endothelial cells are highly dependent on SR-BI and ABCG1, but not on ABCA1 (Rohrer et al 2009). Subsequent research has demonstrated expression of the ectopic β-chain of F0F1 ATPase (β-ATPase) on the endothelial cell surface (Cavelier et al 2012).…”
Section: Transendothelial Hdl Transportmentioning
confidence: 99%
“…Our group found that aortic endothelial cells are able to bind, internalize, and transport both HDLs and lipid-free apoA-I in a specific and saturable manner. 60, 61 Transcytosis of apoA-I through aortic endothelial cells resulted in lipidation of lipid-free apoA-I and was reduced by knockdown of ABCA1 by small interfering RNA, 60,62 providing evidence that ABCA1 is involved in this process. In contrast, binding, uptake, and transendothelial transport of mature HDLs were modulated by ABCG1 and SR-BI, not by ABCA1.…”
Section: Hdl Functionsmentioning
confidence: 99%
“…In contrast, binding, uptake, and transendothelial transport of mature HDLs were modulated by ABCG1 and SR-BI, not by ABCA1. 61 Further research identified a novel mechanism for transport of both apoA-I and HDLs through endothelial cells, in which binding of apoA-I to the β-chain of cell surface F0F1 ATPase expressed on endothelial cells stimulates ATP hydrolysis, and the generated ADP selectively activates P2Y12, leading to internalization and transport of initially lipid-free apoA-I and HDLs. 63 Once apoA-I and HDLs have been loaded with cholesterol, they need to leave the arterial wall to complete reverse cholesterol transport.…”
Section: Hdl Functionsmentioning
confidence: 99%
“…Since the fractional catabolic rate for apoB-48-containing lipoproteins is very high compared to that for apoB-100-containing lipoproteins (Li, 1996), concentrations of VLDL and LDL are very low in wild-type mice and rats compared to humans. In reverse cholesterol transport from peripheral tissue to the liver, high-density lipoproteins (HDLs) receive free cholesterol from macrophages through scavenger receptor type B-I (SR-BI) and ABCs such as ABCA1 (Rohrer, 2009). The free cholesterol transported from macrophages is esterified by lecithin:cholesterol acyltransferase (LCAT) in plasma.…”
Section: Introductionmentioning
confidence: 99%